Integrin β3 Induction Promotes Tubular Cell Senescence and Kidney Fibrosis - Li, Shen; Jiang, Song; Zhang, Qingyan; Jin, Bo; Lv, Daoyuan; Li, Wenju; Zhao, Min; Jiang, Chunming; Dai, Chunsun; Liu, Zhihong (Frontiers in Cell and Developmental Biology, 2021)
Tubular cell senescence is a common biologic process and contributes to the progression of chronic kidney disease (CKD); however, the molecular mechanisms regulating tubular cell senescence are poorly understood. Here, we report that integrin β3 (ITGB3) expression was increased in tubular cells and positively correlated with fibrosis degree in CKD patients. ITGB3 overexpression could induce p53 pathway activation and the secretion of TGF-β, which, in turn, resulted in senescent and profibrotic phenotype change in cultured tubular cells. Moreover, according to the CMAP database, we identified isoliquiritigenin (ISL) as an agent to inhibit ITGB3. ISL treatment could suppress Itgb3 expression, attenuate cellular senescence, and prevent renal fibrosis in mice. These results reveal a crucial role for integrin signaling in cellular senescence, potentially identifying a new therapeutic direction for kidney fibrosis.